Sophia's war : a tale of the revolution - Medal-Winning, Newbery (Scholastic, 2014)
The revolutionary war in America rages, and rages New York City is newly occupied by the powerful British army. Young Sophua Calderwood's beloved soldier brother, William, is being held on a gruesome British prison ship Horrified by the atrocities she sees there, Sophia resolves to avenge his brutal treatment and help advance the patriot cause.